OP33 Broken Hearts: The impact of partner bereavement on cardiovascular risk and disease management. (2nd September 2014) - Carey, IM; Shah, SM; DeWilde, S; Harris, T; Victor, CR; Cook, DG
Abstract : Background: The period immediately following bereavement has been reported as a time of increased risk of cardiovascular events. However this risk has not been well quantified, nor is there good understanding of the potential contribution of the quality of cardiovascular care. Methods: A matched cohort study using 401 general practices in the THIN database during 2005–12. 30, 447 individuals aged 60–89 years at study initiation who experienced partner bereavement during follow up, were matched on age, sex and practice at time of bereavement with controls (n = 83, 558) whose partner was alive. The primary outcome was occurrence of a fatal or non-fatal myocardial infarction (MI) or stroke within 30 days of bereavement. Incidence rate ratios (IRR) from a conditional Poisson model were adjusted for age, smoking, deprivation and history of cardiovascular disease. To investigate cardiovascular disease management, a subset of bereaved individuals with pre-existing coronary heart disease, stroke, diabetes mellitus, or hypertension were matched to controls with similar co-morbidity. Outcomes were key routine annual process measures of care in the year before and after bereavement and cardiovascular medication prescribing, summarised by odds ratios comparing the change between groups. Results: Within 30 days of their partner's death, 50 (0.16%) of bereaved individuals experienced a MI or stroke compared to 67 (0.08%) of non-bereaved controls (IRR=2.20, 95% CI 1.52–3.15). The increased risk was seen in both bereaved men and women, for both MI and stroke separately, and attenuated after 30 days. For cardiovascular disease management in the bereaved, uptake of all annual measures, including monitoring of blood pressure and cholesterol, was lower in the year before bereavement, improving in the year after, whereas in the controls, uptake was relatively stable. There was a transient fall in prescribing in the peri-bereavement period lasting until about 3 months after bereavement. The odds ratio for at least 80% prescription coverage in the 30 days after bereavement was 0.80 (95% CI 0.73–0.88) for lipid-lowering drugs and 0.82 (95% CI 0.74–0.91) for antiplatelets compared with the change in non-bereaved individuals. Conclusion: This study provides evidence that the death of a partner is associated with major acute cardiovascular events with a doubling of risk in the first month. Further, we have shown that patients receive poorer care in the months before and after bereavement, which may contribute to increases in cardiovascular risk. Clinicians need to ensure that quality of cardiovascular care is maintained in the pre- and post-bereavement periods.